The dIANA database - Resource for isotopic paleodietary research in the Baltic Sea area - H. Etu-Sihvola; H. Bocherens; D.G. Drucker; A. Junno; K. Mannermaa; M. Oinonen; J. Uusitalo; L. Arppe (ELSEVIER SCIENCE BV, 2025)
Paleodietary research is a complex field, which requires large sets of background information. Owing to increasing interest and activity in the field, a substantial amount of archaeological isotope baseline data exist for Northern Europe, consisting mainly of animal bone collagen delta C-13, delta N-15, and delta S-34 values. However, the data are scattered into dozens of publications written in multiple languages and less-accessible formats, making the data laborious to use. This article presents the first compilation work of this data, the open access dIANA database (Dietary Isotopic baseline for the Ancient North; https://www.oasisnorth.org/diana.html), aimed to support (paleo)dietary research in the Baltic Sea area. The database work is complemented with new analyses of archaeological and (pre-)modern domestic and wild fauna from Finland and Russia broadening the selection of analysed species in the database. We present and discuss data examples, which on one hand show existing spatiotemporal isotope patterns related to diet and differences in the environmental carbon sources and on the other, also visualize the current status of baseline research and the need for further analyses in the circum-Baltic area.